2016
DOI: 10.3389/fmicb.2016.01915
|View full text |Cite
|
Sign up to set email alerts
|

Combined Whole-Cell High-Throughput Functional Screening for Identification of New Nicotinamidases/Pyrazinamidases in Metagenomic/Polygenomic Libraries

Abstract: Nicotinamidases catalyze the hydrolysis of the amide bond in nicotinamide (NAM) to produce ammonia and nicotinic acid (NA). These enzymes are an essential component of the NAD+ salvage pathway and are implicated in the viability of several pathogenic organisms. Its absence in humans makes them a promising drug target. In addition, although they are key analytical biocatalysts for screening modulators in relevant biomedical enzymes, such as sirtuins and poly-ADP-ribosyltransferases, no commercial sources are av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 56 publications
(89 reference statements)
0
16
0
Order By: Relevance
“…The phylogenetic analysis carried out with MEGA [ 54 ] showed that UbNic clusters in the same clade as the archaeal Pyrococcus horikoshii nicotinamidase [ 13 ] and the recently described polygenomic nicotinamidase PolyNic [ 11 ] ( Fig 2 , cyan). This clade contains a variety of sediment-growing and thermophilic microorganisms from both the Bacteria and the Archaea domains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetic analysis carried out with MEGA [ 54 ] showed that UbNic clusters in the same clade as the archaeal Pyrococcus horikoshii nicotinamidase [ 13 ] and the recently described polygenomic nicotinamidase PolyNic [ 11 ] ( Fig 2 , cyan). This clade contains a variety of sediment-growing and thermophilic microorganisms from both the Bacteria and the Archaea domains.…”
Section: Resultsmentioning
confidence: 99%
“…After sequencing, a putative nicotinamidase sequence was found in fosmid JFF054_F02. Then, the clone containing the latter fosmid was checked for nicotinamidase activity using the previously described pyrazinamide/ammonium ferrous sulfate method [ 11 ]. Briefly, after growing fosmids at 37°C overnight, their pellets were resuspended in a mixture of 20 mM pyrazinamide and 1% ammonium ferrous sulfate dissolved in MilliQ water, and incubated for 1 h at 37°C until an intense orange-red color appeared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrolytic activity of the recombinant enzymes was assayed qualitatively by testing 29 different substrates ( Figure 4A): N 4 -acylated (2'-deoxy)cytidines and cytosines (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16); N 2 -acetylisocytosines (17); chromogenic substrates such as p-nitroacetanilide (18) and p-nitrobenzanilide (19); various p-nitrophenyl (pNP) esters (20)(21)(22)(23)(24); terephthalate derivatives bis(2-hydroxyethyl) terephthalate (26), dimethyl terephthalate (27), and monomethyl terephthalate (28); and the beta-lactam nitrocefin (29). Hydrolysis of chromogenic substrates (18)(19)(20)(21)(22)(23)(24)(25) was analysed spectrophotometrically at 405 nm, and that of other substrates was analysed spectrophotometrically at 240-320 nm and using TLC or HPLC-MS ( Figures S4-S10). All the reactions were monitored up to 24 h. The 8 hydrolases selected from the metagenomic libraries showed different activity profiles towards N-acylated nucleosides harbouring short, bulky aliphatic, aromatic, and heterocyclic groups ( Figure 4B).…”
Section: Substrate Specificity Of the Selected Amidohydrolasesmentioning
confidence: 99%
“…Bacterial gene libraries, constructed from an environment intentionally enriched in N-acylhomoserine lactone-degrading bacteria [22], have been used as well. The acyl transfer activity of amidase in the presence of hydroxylamine, resulting in the spectrophotometric quantification of hydroxamic acid/iron(III) complexes, as well as the whole-cell methods that use the chemical properties of one of the products formed in the amidohydrolase enzymatic reaction to form coloured complexes with stable iron salts have been proposed [23,24]. A system that is based on pro-chromogenic substrates combined with an auxiliary enzyme [25] and an effective approach based on product detection-the product-induced gene expression (PIGEX) [26] system-have also been reported to be suitable for screening of amidohydrolases in metagenomes.…”
Section: Introductionmentioning
confidence: 99%